2009
DOI: 10.1590/s0100-879x2009001200008
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil ingestion reduces the number of aberrant crypt foci and adenoma in 1,2-dimethylhydrazine-induced colon cancer in rats

Abstract: We determined the effect of fish oil (FO) ingestion on colonic carcinogenesis in rats. Male Wistar rats received 4 subcutaneous injections (40 mg/kg body weight each) of 1,2-dimethylhydrazine (DMH) at 3-day intervals and were fed a diet containing 18% by weight FO (N = 10) or soybean oil (SO, N = 10) for 36 weeks. At sacrifice, the colon was removed, aberrant crypt foci were counted and the fatty acid profile was determined. Intestinal tumors were removed and classified as adenoma or carcinoma. Liver and feces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
(23 reference statements)
1
11
0
Order By: Relevance
“…In addition, the results showed that at 4 or 17 weeks after cancer induction by DMH without fish oil supplements (DMH4 and DMH17) the DNA damage, alterations in the expressions of the tested genes and the histopathological lesions, still remained in the tissues. These results are in agreement with previous findings (Cheng et al, 2003, Anilakumar et al, 2004, Kamaleeswari et al, 2006, Jwanny et al, 2009Moreira et al, 2009 andHill et al, 2010).…”
Section: Discussionsupporting
confidence: 94%
“…In addition, the results showed that at 4 or 17 weeks after cancer induction by DMH without fish oil supplements (DMH4 and DMH17) the DNA damage, alterations in the expressions of the tested genes and the histopathological lesions, still remained in the tissues. These results are in agreement with previous findings (Cheng et al, 2003, Anilakumar et al, 2004, Kamaleeswari et al, 2006, Jwanny et al, 2009Moreira et al, 2009 andHill et al, 2010).…”
Section: Discussionsupporting
confidence: 94%
“…Although the application of probiotic with oil, specifically with Lini oleum virginale, to rats was not documented, the effect of fish oil ingestion on colonic carcinogenesis in rats was studied by Moreira et al (2009).…”
Section: Histopathological Changesmentioning
confidence: 99%
“…The results of their experiment indicate that probiotic microorganisms and bioactive compounds could exert a preventive effect on colon carcinogenesis induced by dimethylhydrazine. Although the administration of probiotic with oil, specifically with Lini oleum virginale, to rats was not documented, the effect of fish oil ingestion on colonic carcinogenesis in rats was studied by Moreira et al (2009). The results obtained from our study indicate a positive effect of administering the combination of the strain L. plantarum as probiotic with oil.…”
Section: Discussionmentioning
confidence: 65%